2012
DOI: 10.1165/rcmb.2011-0363oc
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids and Antigen Avoidance Decrease Airway Smooth Muscle Mass in an Equine Asthma Model

Abstract: Recent studies suggest that airway smooth muscle remodeling is an early event in the course of asthma. Little is known of the effects of long-term antigen avoidance and inhaled corticosteroids on chronically established airway remodeling. We sought to measure the effects of inhaled corticosteroids and antigen avoidance on airway remodeling in the peripheral airways of horses with heaves, a naturally occurring asthma-like disease. Heaves-affected adult horses with ongoing airway inflammation and bronchoconstric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
128
3
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(146 citation statements)
references
References 52 publications
9
128
3
4
Order By: Relevance
“…Pulmonary function, BAL fluid and endobronchial biopsies (see below) were obtained at baseline and then 1, 3, 6, 7 and 12 months later. As previously reported, 18 both treatments resulted in improved airway function, although it was more rapidly observed when horses were treated with inhaled fluticasone than with antigen avoidance strategies alone. Conversely, normalisation of BALF neutrophilia was present only when horses were at pasture without hay feeding.…”
Section: Studysupporting
confidence: 73%
See 2 more Smart Citations
“…Pulmonary function, BAL fluid and endobronchial biopsies (see below) were obtained at baseline and then 1, 3, 6, 7 and 12 months later. As previously reported, 18 both treatments resulted in improved airway function, although it was more rapidly observed when horses were treated with inhaled fluticasone than with antigen avoidance strategies alone. Conversely, normalisation of BALF neutrophilia was present only when horses were at pasture without hay feeding.…”
Section: Studysupporting
confidence: 73%
“…The increased (+)insert isoform to total SMMHC ratio during clinical exacerbation is not permanent, as it can be reversed by antigenic avoidance strategies (studies 1 and 3) or by the use of inhaled corticosteroids despite continuous antigen challenge and persisting airway inflammation (study 2 18 ). In study 2, the decrease of the (+)insert isoform to total SMMHC ratio coincided with the normalisation of pulmonary neutrophilia only in the antigen avoidance-treated group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that long‐term dexamethasone and fluticasone treatment did not reverse the airway neutrophilia when RAO horses are kept indoors and exposed to hay even after 6–7 months 6. Other studies showed an additive effect on clinical signs, airway neutrophilia, and inflammatory cytokines in RAO horses when combining corticosteroid treatment with measures to improve air quality 6, 115, 116…”
Section: Treatment For Iadmentioning
confidence: 99%
“…Clinical signs and airway obstruction can be reversed by administration of corticosteroids, bronchodilators, or changing the environment 4, 5, 6. Recurrent airway obstruction principally affects horses over 7 years of age 7, 8.…”
mentioning
confidence: 99%